Multicultural Education Management Strategies to Promote Tolerance and Diversity in the School Environment - Rinovian Rais (Gestion Educativa, 2025)
Multicultural education has become increasingly essential in schools as a response to growing student diversity and the rise of intolerance within educational settings. This study aims to provide a comprehensive analysis of multicultural education management strategies that enhance tolerance and improve diversity management in Indonesian schools. A systematic literature review (SLR) was conducted by examining 28 peer-reviewed articles published between 2015 and 2025 across Scopus, Web of Science, ERIC, and Google Scholar. The analysis employed a thematic synthesis approach to identify effective management strategies, including inclusive leadership, multicultural curriculum implementation, and the strengthening of inclusive school culture. The findings reveal that inclusive leadership serves as a foundational element that guides diversity-oriented policies, while multicultural teaching practices contribute significantly to fostering tolerant cross-cultural interactions among students. Furthermore, an inclusive school culture ensures the sustainability of multicultural values through shared norms and daily social practices. This study concludes that integrated multicultural education management strategies can create safer, more equitable, and more diversity-responsive school environments. The results offer meaningful implications for the development of educational policy and school management practices in Indonesia